Young Children’s Understanding of Fluid Intake. - Williamson, Josh; Howells, Kristy (International Journal of Nutrition, 2019)
Background Coppinger and Howells’ (2019) previously completed an International comparison between primary schools in Ireland and England focusing on children’s understanding of fluid intake. They identified that children under 11 years did not understand the amount of fluid they need each day for good health. Within their sample there was only a limited number of children who were aged 4 – 5 years. This research focuses on this particular age phase and further questions if young children understand fluid intake. Methods 130 children (63 boys and 67 girls, of which 83 were aged 4 and 47 were aged 5) from 4 elementary schools in the South East of England were questioned between January and April 2019 using an adapted version of Coppinger and Howells’ (2019) questionnaire on their understanding of fluid intake and how much they perceived they drank and who supported them in prompting them when to drink. The adaptions were to ensure the questionnaire was age appropriate for younger age range, and included physical visual representations to aid question comprehension. Results 46.9% of children felt they consumed 500ml or under a day. Only 39.6% responded that they were supported by the teacher, also when children were thirsty, if given the option of playing or stopping rehydration and then playing 33.8% would continue to play without drinking. Conclusion Young children in England do not understand fluid recommendations, they were not supported within the school setting by their teacher and more effective resources and strategies are needed to support children’s knowledge.
Keywords: Fluid intake; Children; School; Physical Education